Regulation of Hypoxia-Inducible Factor-1α, Vascular Endothelial Growth Factor, and Angiogenesis by an Insulin-Like Growth Factor-I Receptor Autocrine Loop in Human Pancreatic Cancer - Stoeltzing, Oliver (American Society for Investigative Pathology, 2003)
Activation of the insulin-like growth factor-I receptor (IGF-IR) was recently shown to modulate angiogenesis by up-regulating the expression of vascular endothelial growth factor (VEGF). We hypothesized that inhibiting IGF-IR function would inhibit angiogenesis and growth of pancreatic cancer in vivo and sought to identify major signaling pathways regulated by IGF-IR in pancreatic cancer cells. Human pancreatic cancer cells (L3.6pl) were stably transfected with a dominant-negative form of IGF-IR (IGF-IR DN) or an empty vector (pcDNA). In vitro, IGF-IR DN cells exhibited a decrease in both constitutive and inducible phosphorylation of IGF-IR and Erk1/2. Constitutive expression of nuclear hypoxia-inducible factor-1α and secreted VEGF (P < 0.01) protein levels also were significantly lower in IGF-IR DN cells than in pcDNA cells. In vivo, IGF-IR inhibition led to decreases in pancreatic tumor volume and weight, vessel density, and tumor cell proliferation (P < 0.01 for all) and increases in tumor cell apoptosis (P < 0.02). Our results suggest that autocrine activation of the IGF-IR system significantly affects VEGF expression and angiogenesis in human pancreatic cancer. Thus, IGF-IR may be a valid target in the treatment of pancreatic cancer.